(untitled) (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To explore the coping mechanism of the women suffering with obstetric fistula. Methods: A cross-sectional study was done on 30 women living with OF. Six key informant interviews and three focus group discussions were conducted on health workers, spouses and attendants. Results: The women had lived with OF for a period of one to 40 years. The mean age of respondents was 27 years and the median age at the time they got fistula was 18 years. Seventy two per cent of the women developed OF at less than 25 years of age. Coping with OF included keeping clean and washing all the time (83%), drinking a lot of water (80%) to reduce the smell and sores due to the urine, while 75% ignored people’s negative comments. Others included prayers (57%), seeking refuge at a pastor’s or in a church (30%), eating/drinking less (13%) and engaging in income-generating activities (8.9%). Padding was common to all of them. Conclusions: Women living with OF have two main coping mechanisms: hygiene-focused and psycho-social. These attempts to cope with OF should be further studied, enhanced and supported by authorities, families and communities, to mitigate their suffering before surgical treatment.